Sub-contracting under the JCT 2005 forms - Barnes, Peter, 1954-; Davies, Matthew, 1970- ([Place of publication not identified] : [Wiley], 2008)
These days, subcontractors in the construction industry are generally aware of their rights and obligations, and main contractors and clients' advisers need to keep abreast of developments in subcontract law. As the majority of work is carried out under JCT contracts, all parties need to understand the rights and obligations of the latest JCT 05 suite of subcontracts, against the background of the general principles of contract law. A companion to Peter Barnes' first book, The JCT 05 Standard Building Sub-Contract, this book deals with all the other JCT 05 subcontracts including:<br.
Chapter 12: Termination of Sub-contractChapter 13: Settlement of Disputes; Mediation; Adjudication; Arbitration; Litigation; Table of Cases; Table of Statutes and Regulations; Subject Index
Print version record.
John Wiley and Sons
Keywords: Construction industry -- Subcontracting; Construction -- Industrie -- Sous-traitance.; Construction industry -- Subcontracting